The Urgency of Islamic Education in the Family to Overcome Deviant Behavior at the Mawlid Celebration of the Prophet - Masdin Masdin; Usman Usman (Edumaspul: Jurnal Pendidikan, 2023)
The Islamic community in Dasan Agung Village, in celebrating the Birthday of the Prophet Muhammad SAW, is still dualism and two groups. One group concentrated on the mosque, and the other focused on the highway. Groups conducting mosque-centred celebrations carry out various activities to increase religious knowledge and faith one month before the core celebration. This study aims to determine the implementation of Mawlid celebrations in Dasan Agung, more specifically, the pattern of education applied by parents to children and the application of Islamic education to avoid deviations from Mawlid celebrations in Dasan Agung sub-district. The method used is qualitative, exploratory data obtained from observations and interviews. The results showed that the celebration of Prophet Muhammad's birthday in Dasan Agung village was carried out in two versions: celebrations centred on mosques and highways. Celebrations centred on the road, from preparation to the day of implementation of the teachings of Islam, far from religious demands, can even be declared as misleading celebrations.